0150 Respiratory effects of an exposure to wheat dust among grain workers and farmers: a longitudinal study. (23rd June 2014) - Wild, Pascal; Dorribo, Victor; Pralong, Jacques; Reboux, Gabriel; Oppliger, Anne; Danuser, Brigitta; Krief, Peggy; Niculita-Hirzel, Hélène
Abstract : Objectives: Agriculture is considered one of the occupations most at risk of acute or chronic respiratory problems. The aim of our study was to determine from which level of exposure to organic dust the respiratory function is chronically affected in workers involved in wheat grain or straw manipulation and to test if some of these working populations can recover their respiratory function after an exposure decrease. Method: 87 workers exposed to wheat dust: farmers, harvesters, silo workers and livestock farmers and 62 non exposed workers, were included into a longitudinal study comprising two visits at a six months interval with lung function measurements and symptom questionnaires. Cumulative and mean exposure to wheat dust were generated from detailed work history of each worker and a task-exposure matrix based on task-specific exposure measurements. Immunoglobulins (IgG and IgE) specific of the most frequent microorganisms in wheat dust have been determined. Results: FEV1 decreased significantly with the cumulative exposure and mean exposure levels. The estimated decrease was close to 200 mL per year of high exposure, which corresponds roughly to levels of wheat dust higher than 10 mg/m 3 . Peak expiratory flow and several acute symptoms correlate with recent exposure level. Recovery of the respiratory function six months after exposure to wheat dust and evolution of exposure indicators in workers blood (IgG and IgE) will be discussed. Conclusions: These results show a chronic effect of exposure to wheat dust on bronchial obstruction. Short term effects and reversibility will be assessed using the full study results.